The Church in the face of today’s moral controversies - Mesquida Sampol, Joan (Razón y fe, 2021)
While hegemonic humanism declares that we are all masters of our own bodies, the Church opposes this erroneous conception of the person with the rigidity of moral norms that provoke the bewilderment of many believers. This confusion can vanish if this moral rigidity gives way to a different discourse, one that highlights the shortcomings of exclusive humanism while at the same time presenting a Christian humanism that emphasizes the sense of human freedom and the role of the moral conscience in the face of certain dogmatisms.